Synchronous primary ovarian and endometrial cancers: a series of cases and a review of literature - Dębska-Szmich, Sylwia; Czernek, Urszula; Krakowska, Magdalena; Frąckowiak, Marta; Zięba, Agnieszka; Czyżykowski, Rafał; Kulejewska, Dominika; Potemski, Piotr (Menopause Review/Przegląd Menopauzalny, 2014)
Synchronous cancers account for 0.7-1.8% of all gynecologic cancers. Among them, synchronous ovarian and endometrial cancers are predominant (40-53%). Patients with synchronous cancers have better prognosis than those with single disseminated cancer. We present 10 patients with synchronous ovarian and endometrial cancers who were treated at the Chemotherapy Department of the Medical University of Lodz in 2009-2013. The most often reported symptom of the disease was abnormal vaginal bleeding (6 patients). The range of the patients’ age was 48-62 and the median age was 56. Five patients had stage I of ovarian cancer, single patients had stage IIA, IIB and IIIB, 2 patients had stage IIIC. Three patients had I, 5 – II, and 2 – III stage of endometrial cancer. All patients had endometrioid type of endometrial cancer, 7 of them had also the same histological type of ovarian cancer. All patients had adjuvant chemotherapy because of ovarian cancer, none of them had adjuvant radiotherapy. One patient was lost to follow up. For other patients a median follow up was 13 months (range: 3-53 months). One patient experienced relapse, all patients are alive. Synchronous ovarian and endometrial cancers are usually diagnosed at an earlier stage, have lower histological grade and better prognosis than single cancers. The most common histological type of both endometrial and ovarian cancers is endometrioid carcinoma. The first symptoms reported by our patients and the course of the disease were concordant with data from the literature.